The effects of eight weeks circuit resistance training on some endothelial markers, blood pressure and lipid profiles in pre-hypertensive obese women - Hengameh Moradian; Sedigheh Hosseinpour Delavar; Ali Zabet (فیزیولوژی ورزش و فعالیت بدنی, 2022)
Purpose: Endothelial dysfunction is the fastest symptom of vascular dysfunction in obese individuals also the onset of pre-hypertension development and along with lipid profiles can lead to dangerous cardiovascular diseases. The aim of this study was to investigate the effects of eight weeks circuit resistance training (CRT) on some endothelial markers, blood pressure and lipid profiles in pre-hypertensive obese women.Methods: For this purpose, 24 pre-hypertensive obese women (age 44.73 ± 4.43 years, body max index 32.39 ± 3.8kg/m2, systolic blood pressure 13.21 ± 0.61 and diastolic 8.65 ± 0.33 mmHg) were randomly assigned to CRT and Control groups. CRT group performed circuit resistance training for eight weeks, three sessions per week and each session was 50 to 60 minutes. Resistance movements performs in the form of three circles and nine stations, including four upper body movements (chest press, lateral pull down, seated cable row, biceps cable curl) and three lower body movements (leg press, seated leg extension, leg curl), and two core-body movements (crunch and back extension) with 12-15 repetitions, which according to the recommendations of the American Heart Association was 40% 1RM for upper body and 60% 1RM for lower body movements. Control group didn’t have any training activities during the intervention. Blood pressure, anthropometric measurements and blood samples were collected 48 hours before the intervention and 48 hours after the last training session.Results: The results showed that eight weeks of circuit resistance training can significantly reduce body fat percentage (P = 0.005), waist to hip ratio (P = 0.043), systolic (P = 0.001) and diastolic (P = 0.002) blood pressure and triglycerides (P = 0.043) and significantly increase nitric oxide levels (P= 0.008).Conclusion: It seems that eight weeks of CRT can decrease blood pressure by decline some lipid profile and also increase in nitric oxide levels by increase in capillary network in active muscles, and vascular flexibility.